POSHAN’s abstract digest on maternal and child nutrition research - Issue 43 - Avula, Rasmi (International Food Policy Research Institute, 2022)
In this 43rd issue of the POSHAN Abstract Digest, we bring to you a collection of interesting articles on various topics pertaining to maternal and child nutrition. This short issue features studies that assess annual trends in wasting and anemia among children under the age of 5 years using national survey data, the relationship of anthropometric failure with child mortality, and the effectiveness of participatory women’s groups scaled up by the public health system to improve birth outcomes. There are also two studies focusing on the role of community health workers (CHWs), namely in providing maternal nutrition counselling to improve child nutrition, and the effect of home visits on infant health.